Web-Based Educational Game Development to Improve Elementary School Students' Learning Efficiency and Interest - Asri Asri; Fitriyani Fitriyani; Katie Katie; Akbar Iskandar (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2025)
The development of digital technology has encouraged the use of interactive learning media in elementary education. However, various digital innovations have not fully demonstrated a consistent pedagogical impact on student learning efficiency and interest, especially when media development emphasizes technical aspects rather than instructional design and outcome-based evaluation. This study aims to develop and evaluate a web-based educational game designed to improve elementary school students' learning efficiency and interest. The study used a design and development research approach, which included needs analysis, design, development, and evaluation stages. The research subjects consisted of 32 fourth-grade elementary school students. Data were collected through learning outcome tests (pre-test and post-test), task completion time measurements, learning interest questionnaires, and classroom observations. Quantitative analysis using a paired-sample t-test showed a significant increase in student learning outcomes after using the educational game (t(31) = 9.27; p < 0.001; d = 1.64) and a significant decrease in task completion time (t(31) = 8.11; p < 0.001; d = 1.43). Students' learning interest scores were in the high category (M = 4.21). These findings indicate that pedagogically designed web-based educational games are capable of simultaneously increasing the efficiency and learning interest of elementary school students.